Glasdegib in combination with cytarabine and daunorubicin in patients with AML or high‐risk MDS: Phase 2 study results. Issue 11 (9th September 2018) - Cortes, Jorge E.; Douglas Smith, B.; Wang, Eunice S.; Merchant, Akil; Oehler, Vivian G.; Arellano, Martha; DeAngelo, Daniel J.; Pollyea, Daniel A.; Sekeres, Mikkael A.; Robak, Tadeusz; Ma, Weidong Wendy; Zeremski, Mirjana; et al.
Abstract: Glasdegib is a Hedgehog pathway inhibitor. This ongoing, open‐label, phase 2 study (NCT01546038) evaluated glasdegib plus cytarabine/daunorubicin in patients with untreated acute myeloid leukemia (AML) or high‐risk myelodysplastic syndromes (MDS). Patients received glasdegib 100 mg orally, once daily in continuous 28‐day cycles from day −3, with intravenous cytarabine 100 mg/m 2 on days 1‐7 and daunorubicin 60 mg/m 2 on days 1‐3. Patients in remission then received consolidation therapy (2‐4 cycles of cytarabine 1 g/m 2 twice daily on days 1, 3, 5 of each cycle), followed by maintenance glasdegib (maximum 6 cycles). Primary endpoint was complete remission (CR) in patients aged ≥55 years. Secondary endpoints included overall survival (OS), safety and outcome by mutational status. Patients had a median (range) age of 64.0 (27‐75) years, 60.0% were male, and 84.5% were white. In 69 evaluable patients, 46.4% (80% confidence interval [CI]: 38.7‐54.1) achieved investigator‐reported CR. Among patients ≥55 years old ( n = 60), 40.0% (80% CI 31.9‐48.1) achieved CR. Among all 69 patients, median OS was 14.9 (80% CI 13.4‐19.3) months, with 12‐month survival probability 66.6% (80% CI 58.5‐73.4). The most common treatment‐related adverse events (≥50% patients) were diarrhea and nausea. There were no significant associations between mutational status (12 genes) and clinical response, suggesting potential benefit across diverse molecular profiles. Glasdegib plus cytarabine/daunorubicin was well tolerated and associated with clinical activity in patients with untreated AML or high‐risk MDS. A randomized phase 3 trial of glasdegib in combination with chemotherapy (7 + 3 schedule) is ongoing.